The Role of a Sport in Healthy Lifestyle - Baxtiyarovich, Asatullayev Rustamjon; Alijonovich, Yusupov Davlat (American Journal of Bioscience and Clinical Integrity, 2025)
this document explores the vital role of sport in maintaining a healthy lifestyle. It highlights the physical, mental, and social benefits of regular physical activity, emphasizing its contribution to cardiovascular health, stress reduction, and community building. The paper also discusses how sport fosters discipline, goal-setting, and personal growth. Additionally, it addresses the importance of selecting the right sport based on individual abilities and overcoming barriers to accessibility. The document concludes by stressing the need for a balanced approach to integrating sport into daily life, ensuring long-term well-being and fulfillment.